Partnerships in Practice: Producing New Design Knowledge with Users When Developing Performance Apparel Products. (2nd September 2018) - Morris, Kristen D.; Ashdown, Susan P.
Abstract: The performance apparel industry has a long history of engaging consumers, or users, in the apparel product development process to enhance existing products and inspire innovations. New design knowledge, in the form of user insights, can drive innovation and meet the exacting needs of the user. However, the methods that apparel product developers use to engage users in the design process remains relatively underexplored regarding the types of new design knowledge generated by each method. There exists a gap in the literature regarding design knowledge creation in the performance apparel industry, particularly regarding user engagement. Therefore, the primary purpose of this research was to explore how new design knowledge is produced with users when creating performance apparel. To achieve this goal, the researchers conducted interviews with 13 design professionals who worked at performance apparel brands. Their detailed accounts were used to describe the context of user involvement, explore the research methods product developers use to produce knowledge with users and the links between practices and knowledge production as framed through Nonaka's Knowledge-Creating Theory.